Moving Toward a Global Age‐Friendly Ecosystem. Issue 9 (23rd July 2020) - Fulmer, Terry; Patel, Pinkey; Levy, Nicole; Mate, Kedar; Berman, Amy; Pelton, Leslie; Beard, John; Kalache, Alexandre; Auerbach, John
Abstract : The designation of "age friendly" has clearly engaged the attention of scholars and leading experts in the field of aging. A search of PubMed references citing the term produced 15 results in the 5‐year period from 2006 to 2011; that number increased to 572 in the period from 2015 to 2019. The work, notably led by the World Health Organization with the initiation of age‐friendly cities and age‐friendly communities, has now sparked a movement for the creation of age‐friendly health systems and age‐friendly public health systems. Now more than ever, in an era of pandemics, it seems wise to create an ecosystem where each of the age‐friendly initiatives can create synergies and additional momentum as the population continues to age. Work of a global nature is especially important given the array of international programs and scientific groups focused on improving the lives of older adults along with their care and support system and our interconnectedness as a world community. In this article, we review the historical evolution of age‐friendly programs and describe a vision for an age‐friendly ecosystem that can encompass the lived environment, social determinants of health, the healthcare system, and our prevention‐focused public health system. Abstract : See related editorial by Terrie T. Wetle in this issue.